2016
DOI: 10.1039/c6gc00432f
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite type oxide-supported Ni catalysts for the production of 2,5-dimethylfuran from biomass-derived 5-hydroxymethylfurfural

Abstract: Hydrogenolysis of biomass-derived 5-hydroxymethylfurfural to 2,5-dimethylfuran was performed over perovskite type oxide-supported Ni catalysts. A yield of 98.3% of 2,5-dimethylfuran was obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 117 publications
0
40
0
Order By: Relevance
“…Unlike Cu‐based catalysts, Ni catalysts exhibited over hydrogenation and ring opening of furan derivatives . Nakagawa et al.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 95%
“…Unlike Cu‐based catalysts, Ni catalysts exhibited over hydrogenation and ring opening of furan derivatives . Nakagawa et al.…”
Section: Catalytic Hydrogenation And/or Hydrogenolysis Of Biomass‐dermentioning
confidence: 95%
“…[31] Ebitani and co-workers reported ab imetallic Pd 50 Au 50 /C catalyst-catalyzed HDO of HMF to DMF in the presence of HCl under an atmospheric H 2 pressure. [37,38] Li and co-workers reported as eries of studies concerning the catalytic conversion of HMF over non-noble-metal catalysts such as Raney Ni, Ni-nanoparticles-inlaid Ni-phyllosilicate, Ni/Al 2 O 3 ,a nd mineral-derived Cu catalysts. [33] Hansen et al reported the catalytic conversion of HMF over aC udoped porousm etal oxide in supercritical methanol,a nd ac ombined yield [DMFa nd 2,5-dimethyltetrahydrofuran (DMTHF)]o f5 8% was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Since emphasis was early put on the need for an auxiliary metal or for surface acidic sites to obtain a selective catalyst, the catalytic properties of monometallic catalysts based on non‐noble metals have been paradoxically less explored . Ni‐based catalysts are known for their hydrogenation ability, but successes in the selective conversion of HMF have mostly been achieved with bimetallic or multifunctional catalysts, e. g ., Ni‐W 2 C/C, Ni−Fe/CNTs (carbon nanotubes), Ni/LaFeO 3 and others …”
Section: Introductionmentioning
confidence: 99%